A giant rapidly progressive breast phyllodes tumour causing a skin rupture. A case report and literature review - Saad Abdalla Al-Zawi, Abdalla; Salih, Ali; Chicken, Wayne; Osayi, Kingsley; Comez, Turhan; Barron, Marina; Adamczyk, Beata (Journal of Medical Science, 2017)
Large phyllodes tumours may behave in a rare way, in this paper we present a case of large phyllodes tumour with a female lady aged 42. The tumour caused a skin rupture due to rapid growth.
Keywords: breast phyllodes; mammogram; mastectomy